Síntese, caracterização e propriedades fotocatalíticas de nanocompósitos de TiO2/GO e TiO2/GO/SrTiO3 - Mayra do Carmo Siqueira (2021)
Industrial processes have led to the disposal of effluents from complex matrices with the potential to contaminate watercourses. In particular, the search for nanomaterials capable of degrading pollutants with good performance and chemical stability under different application conditions has been the objective of many studies in the literature. Nanotechnology development has promoted significant advances in the combination of nanomaterials capable of producing cleaner energy or even photodegrading substances with high toxicity. In this work, crystalline nanoparticles (NPs): anatase TiO2 (7 nm); SrTiO3 (STO - 13 nm) and GO nanostructures were synthesized. The synthesis of TiO2 and STO was carried out using microwave-assisted hydrothermal method, which has been applied as a more efficient and environmentally friendly, due to its low reagent and energy consumption to obtain nanoparticulate materials. The GO (0.82 nm spacing between sheets) was obtained from the modified Hummers methodology, which is a methodology already applied in the literature that allows obtaining materials with high surface area and adsorptive capacity. TiO2/GO nanocomposites (NCs) were prepared according to variation of GO concentration in relation to TiO2 (0.25, 0.50, 1.00 and 2.00% wt.%) as well as TiO2/GO/STO NCs containing 0.50 wt.% of GO with the STO proportions (0.25, 0.50, 1.00 and 2.00 wt.%) in relation to TiO2. The NCs were submitted to 180 minutes of reaction in a 10-5 mol. L-1 rhodamine B solution under UV-C radiation. The best results obtained were for the NC TiO2-1.00% GO and for the NC TiO2-0.50% GO-0.25% STO, which showed percentages of degradation of rhodamine B of 95 and 91%, respectively.